Low-frequency impact sound of timber floors: A finite element–based study of conceptual designs. Issue 1 (March 2021) - Olsson, Jörgen; Linderholt, Andreas
Traditionally, product development concerning acoustics in the building industry is measurement oriented. For lightweight floors, frequencies that are lower than the frequency range for heavy concrete floors are an issue. The frequency range of from 50 Hz down to 20 Hz influences the human perception of impact sound in multi-story apartment buildings with lightweight floor constructions, such as timber floors, for example. It is well known that a lower frequency range of interest makes finite element simulations more feasible. Strategies for reducing impact sound tend to be less straightforward for timber floors because they have a larger variation of designs when compared to concrete floors. This implies that reliable finite element simulations of impact sound can save time and money for the building industry. This study researches the impact sound transmission of lightweight timber floors. Frequency response functions, from forces on excitation points to sound pressure in the receiving cavity below, are calculated. By using fluid elements connected to reflection-free boundary elements under the floors in the models, the transmission and insulation can be studied without involving reverberation. A floor model with a hard screed surface will have a larger impact force than a softer floor, although this issue seems less pronounced at the lowest frequencies. To characterize floor surfaces, the point mobilities of the impact points are also calculated and presented. The vibration and sound transmission levels are dependent on the selection of the excitation points.